The Effect of Self Organized Learning Environment (SOLE) Model Towards Students’ Critical Thinking Skills in Buffer Solution Topic - Dewi, Lutfi Sahitta; Rahmania, Sri (LAVOISIER: Chemistry Education Journal, 2025)
Conventional learning models in learning activities is one of the factors causing critical thinking skills of students at SMA N 15 Semarang become low. Therefore, an interactive learning model is needed to develop students' critical thinking skills. The purpose of the study was to determine the effect of Self Organized Learning Environment (SOLE) model towards students' critical thinking skills. This research used the pretest-posttest control group design. Sampling technique used random sampling and data collection techniques using observation, interviews and tests. The test instrument was made using indicators of critical thinking skills according to Ennis. The data analysis technique used the N-Gain Score Test and the Independent Sample t-test. The t-test score results 0.000 0.05 meaning that Ha is accepted and the SOLE model has effect towards students' critical thinking skills. The critical thinking skills of students based on n-gain value is also shown improved. The experimental class got 0.71 with high criteria, while the control class got a value of 0.48 with medium criteria.